Exploring Divergent Patterns in Racial Identity Profiles Between Caribbean Black American and African American Adolescents: The Links to Perceived Discrimination and Psychological Concerns. Issue 4 (October 2016) - Sanchez, Delida; Bentley‐Edwards, Keisha L.; Matthews, J. S.; Granillo, Teresa
Abstract : Using cluster analyses, this study explored the relations among racial identity, perceived discrimination, and psychological concerns among 189 Caribbean Black American and African American adolescents. Findings showed that for all participants, less mature racial identity profiles were significantly related to perceived discrimination and psychological concerns. However, nuances in racial identity profiles between Caribbean Black American and African American participants suggest subtle ethnic group differences in racial identity development. Implications for practitioners and research are discussed. Usando análisis cluster, este estudio exploró las relaciones entre identidad racial, discriminación percibida y preocupaciones psicológicas en 189 adolescentes afroamericanos y americanos negros caribeños. Los hallazgos mostraron que, para todos los participantes, los perfiles de identidad racial menos maduros estaban significativamente relacionados con una discriminación percibida y preocupaciones psicológicas. Sin embargo, los matices de los perfiles de identidad racial entre los participantes afroamericanos y americanos negros caribeños sugieren unas diferencias sutiles entre ambos grupos étnicos en el desarrollo de la identidad racial. Se discuten las implicaciones para practicantes e investigadores.